2008
DOI: 10.1128/jvi.01023-07
|View full text |Cite
|
Sign up to set email alerts
|

Antigen-Specific B-Cell Responses to Porcine Reproductive and Respiratory Syndrome Virus Infection

Abstract: Porcine reproductive and respiratory syndrome virus (PRRSV) causes an acute, viremic infection of 4 to 6 weeks, followed by a persistent infection lasting for several months. We characterized antibody and B-cell responses to viral proteins in acute and persistent infection to better understand the immunological basis of the prolonged infection. The humoral immune response to PRRSV was robust overall and varied among individual viral proteins, with the important exception of a delayed and relatively weak respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
73
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(78 citation statements)
references
References 63 publications
(76 reference statements)
4
73
1
Order By: Relevance
“…Factors such as extensive viral genetic and antigenic diversity, large populations of animals in regions of dense swine production that facilitate spread of virus, persistence of virus for extended periods in pigs during which it can be transmitted to susceptible animals, and inability of current vaccines to prevent infection in populations all contribute to the problem of PRRSV spread and persistence. Pigs generate a well-documented humoral immune response against PRRSV (Molina et al, 2008;Mulupuri et al, 2008;Nelson et al, 1994). However the slow kinetics, small magnitude and limited breadth of protection observed from the neutralizing antibody response have led to the belief that it is not an important factor, nor realistic approach, for achieving widespread protection against PRRSV (reviewed in Darwich et al, 2010;Murtaugh and Genzow, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Factors such as extensive viral genetic and antigenic diversity, large populations of animals in regions of dense swine production that facilitate spread of virus, persistence of virus for extended periods in pigs during which it can be transmitted to susceptible animals, and inability of current vaccines to prevent infection in populations all contribute to the problem of PRRSV spread and persistence. Pigs generate a well-documented humoral immune response against PRRSV (Molina et al, 2008;Mulupuri et al, 2008;Nelson et al, 1994). However the slow kinetics, small magnitude and limited breadth of protection observed from the neutralizing antibody response have led to the belief that it is not an important factor, nor realistic approach, for achieving widespread protection against PRRSV (reviewed in Darwich et al, 2010;Murtaugh and Genzow, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of the humoral immune response to PRRSV focused mainly on detection of antibodies to viral structural proteins, especially N (9,22,26,29). Several studies showed that certain nsps, such as nsp1 and nsp2, are highly immunogenic (4,7,13,24,25).…”
Section: Discussionmentioning
confidence: 99%
“…Immunization with exogenous GP5 or encoding GP5 plasmids (Lopez and Osorio, 2004;Pirzadeh and Dea, 1998) has been shown to induce neutralizing antibodies. However, the neutralizing antibodies against GP5 in pigs infected with PRRSV were delayed approximately 2 weeks compared with antibodies to N and Nsp2 (Mulupuri et al, 2008) suggesting that the neutralization antibody inducing function of GP5 was modulated by the other PRRSV proteins during PRRSV infection. This indicates that expressing GP5 in PRRSV a susceptible cell before virus infection is a preferable method to investigate the role of GP5 in PRRSV infection.…”
Section: Discussionmentioning
confidence: 85%
“…Immunization with exogenous GP5 or exposure to native GP5 by means of DNA immunization can provide some degree of immune protection to PRRSV infection in pigs (Lopez and Osorio, 2004). However, in PRRSV infected pigs, the production of antibodies against GP5 is delayed by approximately 2 weeks compared with the antibodies to N and Nsp2 (Mulupuri et al, 2008).…”
Section: Introductionmentioning
confidence: 97%